Incidental Prostate Infections: Developing the Prostate Microbiome. (28th October 2020) - Daniel, D; Zuretti, A
Abstract: Introduction/Objective: About 1 in 9 men will be diagnosed with prostate cancer in their lifetime. The traditional method of diagnosis is via a 12 core, trans-rectal biopsy. While this has been an appropriate method of investigation, a rectal approach to the prostate core made it difficult to differentiate prostatic bacterial infection from fecal contamination. Utilizing a sterile trans-perineal approach for biopsy, we were able to establish a true microbiome of the prostate, without contamination. Methods: This is a prospective, IRB approved study. Men who were required to have prostate biopsies were offered a trans-perineal or trans rectal method of biopsy. Those who opted for trans-perineal biopsy with a negative urine culture met the inclusion criteria. Urine culture was performed prior to scheduling for the procedure. At time of biopsy, sterile cultures were taken from the rectum and one randomly selected prostate core. Cultures were grown for 5 days, and the results were recorded. Results: Of the 93 patients who met inclusion criteria, eight men contained various bacteria within the sterilely accessed prostate core. Of the eight prostate cores which grew positive cultures, five of those patients had an isolated prostatic infection, without rectal or urinary co-infection. The most common infections included E. coli (n=2) and Klebsiella species (n=3). Conclusion: New techniques in the performance of prostate biopsy provides the microbiology laboratory unique opportunities for investigation. This is the beginning of the study of the prostate microbiome, and future correlation with prostate cancer and isolated prostate infection are areas of future inquiry.